Mitophagy activation repairs Leber’s hereditary optic neuropathy-associated mitochondrial dysfunction and improves cell survival - Sharma, Lokendra Kumar (Hum Mol Genet, 2019)
Leber’s hereditary optic neuropathy (LHON) is a classical mitochondrial disease caused by mutations in the mitochondrial DNA encoding complex I subunits. Oxidative stress associated with complex I defect has been implicated in developing LHON phenotype such as retinal ganglion cell (RGC) death and loss of vision. However, the mechanism of LHON pathogenesis is still not very clear and thus no effective therapies are available to date. Using cybrid models for LHON, we show that autophagy is significantly compromised in cells carrying LHON-specific mtDNA mutations, which results in reduced clearance of dysfunctional mitochondria contributing to cell death. We further show that pharmacological activation of autophagy selectively clears the damaged mitochondria and thus repairs mitochondrial defects and improves overall cell survival in LHON cell models. Our results suggest that compromised autophagy is the missing link from oxidative stress to LHON pathogenesis. Activation of mitophagy ameliorates mitochondrial defects and exerts a protective role by improving cell survival in cells carrying LHON mutations that could be utilized as a potential therapeutic target for LHON treatment.